Effect of the Addition of 4 wt% Zr to BCC Solid Solution Ti52V12Cr36 at Melting/Milling on Hydrogen Sorption Properties - Kamble, Amol; Sharma, Pratibha; Huot, Jacques (Frontiers in Materials, 2022)
Addition of 4wt%Zr to Ti52V12Cr36 alloy was made in two different ways: arc-melting or ball milling. The cast alloy showed rapid hydrogen absorption up to 3.6 wt% of hydrogen capacity within 15 minutes. Ball milling this sample worsened the kinetics and no hydrogen absorption was registered when milling was done for 30 or 60 minutes. When zirconium is added by ball milling, the kinetic is slower than when addition is by arc melting. This is due to the fact that when added by milling, zirconium does not form a ternary phase with Ti, V and Cr but instead is just dispersed on the particles’ surface.